Strong association of common variants in the IGF2BP2 gene with type 2 diabetes in Lebanese Arabs - Nemr, Rita (2012)
Objective Several genome-wide association studies and replication analyses have identified common variation at the insulin-like binding protein 2 (IGF2BP2) gene to be associated with type 2 diabetes (T2DM). The aim of this study was to replicate in a Lebanese Arab population identified associations of IGF2BP2 variants rs4402960 and rs1470579 with T2DM. Methods This case–control study involved 544 T2DM patients and 606 control subjects. Genotyping was done by the allelic exclusion method. Results T allele of rs440960 (P = 6.5 × 10−6) and C allele of rs1470579 (P = 5.3 × 10−4) were significantly associated with T2DM; both SNPs were in strong LD (D′ = 0.83, r2 = 0.58). While both IGF2BP2 SNPs were significantly associated with T2DM under additive and recessive models, only rs4402960 remained significantly associated with T2DM under the dominant model. Taking the common rs4402960/rs1470579 GA haplotype as reference, multivariate analysis confirmed the positive association of TC (P = 0.009; OR, 1.43; 95%CI, 1.09–1.87), and TA (P < 0.001; OR = 5.49; 95%CI = 2.09–14.39) haplotypes with increased T2DM risk. These differences remained significant after applying the Bonferroni correction for multiple testing. Conclusion We validate that IGF2BP2 susceptibility variants rs4402960 and rs1470579 associate with T2DM in Lebanese Arabs.